INCREASING THE ADSORPTION SURFACE AREA OF ACTIVATED CARBON (Journal of Engineering, 2008)
Experiments were carried out to study the effect of various activated carbon-glass beads weight ratios, influent phenol concentrations, flow rate and bed depth on the performance of fixed bed adsorption column. The equilibrium data and interparticle diffusion coefficients obtained from separate experiments in a batch adsorber were fitted with theoretical model. The effect of adding different weight ratios of an inert solid material to the adsorbent bed in the adsorption process of phenol onto activated carbon was carried out. Adding 5 wt % glass beads to the activated carbon bed reduces the amount of activated carbon by 5% and increases the operating time by 80%.. Increasing the glass beads from 10 wt % and above makes the adsorption process inefficient compared with 0 wt % glass beads. A mathematical model was achieved to describe the mass transfer kinetics in a fixed bed column. The results show that the mathematical model includes external mass transfer and pore diffusion using nonlinear isotherms, provides a good description of the adsorption process for phenol in fixed bed adsorber.